Sodium carboxymethyl chitosan as a fixative for eau de cologne - Wannaruemon S. (2014)
Purpose: To study the characteristics of sodium carboxymethyl chitosan (SCM-chitosan) as a fixative for eau de cologne product. Methods: SCM-chitosan was prepared by carboxymethylation reaction of chitosan with monochloroacetic acid. The solubility of SCM-chitosan was investigated in water and ethanol. Sixteen perfume compounds which consisted of four chemical types - alcohols, ketones, aldehydes and ethers - were selected for eau de cologne preparation. The turbidity of the products prepared was monitored over 21-day aging period. Those showing no turbidity were selected for fixative studies with SCM-chitosan. The fixative effect of SCM-chitosan was evaluated by head space gas chromatography at different temperatures (25, 35 and 53 °C). Results: The prepared SCM-chitosan was soluble in water but insoluble in ethanol. The optimum ratio between water and ethanol that could completely dissolve 0.1 % SCM-chitosan was 2:3 v/v. SCM-chitosan showed significant fixative effect (3.9 - 92.2 %) on p-cresyl methyl ether (10 % in dipropyleneglycol). Fixative efficiency increased from 3.9 % at 25°C to 42.1 % at 35 °C and 92.2 % at 53 °C. However, products containing benzyl alcohol, ethyl acetoacetate and 94085 floral-fruity showed precipitation after 21 days. Conclusion: The results obtained indicate that SCM-chitosan could be used as a potential fixative for eau de cologne products. © Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, Benin City, 300001 Nigeria. All rights reserved.